2018
DOI: 10.1002/jcb.27494
|View full text |Cite
|
Sign up to set email alerts
|

CCL17‐CCR4 axis promotes metastasis via ERK/MMP13 pathway in bladder cancer

Abstract: As an important chemokine receptor, the role of CCR4 in the progression of bladder cancer (BC) remains unknown. In this study, we have shown that CCR4 expression was upregulated in bladder carcinoma tissues compared with adjacent nontumor tissues. Kaplan-Meier survival analysis revealed that CCR4 expression was an independent prognostic risk factor in BC patients, and the addition of CCL17 induced CCR4 production and promoted migration and invasion of BC cells. In addition, CCR4 knockdown significantly attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Stimulation of regulatory T cells with CCL17/CCR4 can phosphorylate ERK1/2,36 and CCR4 up-regulates MMP13 expression through ERK1/2 in colorectal cancer 37. Similarly, Zhao et al, also reported that CCL17/CCR4 axis can induce the metastasis of bladder cancer cells by promoting ERK1/2 signaling and MMP13 expression 19. CXCL12/CXCR4 promoted laryngeal and hypopharyngeal squamous cell carcinoma metastasis through MMP-13-dependent invasion via the ERK1/2 signaling pathway 20.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Stimulation of regulatory T cells with CCL17/CCR4 can phosphorylate ERK1/2,36 and CCR4 up-regulates MMP13 expression through ERK1/2 in colorectal cancer 37. Similarly, Zhao et al, also reported that CCL17/CCR4 axis can induce the metastasis of bladder cancer cells by promoting ERK1/2 signaling and MMP13 expression 19. CXCL12/CXCR4 promoted laryngeal and hypopharyngeal squamous cell carcinoma metastasis through MMP-13-dependent invasion via the ERK1/2 signaling pathway 20.…”
Section: Discussionmentioning
confidence: 92%
“…MMP13 is known to promote BC cell invasion and metastasis and is associated with overall survival of BC patients 18. ERK1/2, as well as its downstream signaling effector MMP13, is some of the mechanism by which CXCL12/CXCR4 or CCL17/CCR4 regulates cell invasion and migration of laryngeal and hypopharyngeal squamous cell carcinoma and bladder cancer 19,20. However, how CCL17 regulates ERK1/2 pathway directly or indirectly remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that CCR4 regulated the traffic of dendritic cells, recirculated T cells from tissue to draining lymph nodes, and migrated T cells to ectopic lymphoid tissue (24,25). CCR4 has also been found to be expressed in some epithelial cells, such as lung, colon, and bronchial epithelial cells (26,27) and to play an important role in many malignant tumors, including solid and hematological tumors (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…MMP13 level in ascitic fluid was seemed to be associated with shorter survival. Thus, MMP13 could be a potential prognostic factor and plays an important role in ovarian cancer metastasis [29,30].…”
Section: Discussionmentioning
confidence: 99%